Tres usurpadores godos : tres estudios sobre la tiranía en el reino visigodo de Toledo - Barroso Cabrera, Rafael, (Access archaeology., 2021)
This text presents a study of three famous usurpations of the Visigothic period: the uprising of Prince Hermenegild (579-585); the rebellion of Duke Argimundo at the beginning of the reign of Recaredo; and Duke Theudemirus and the role he played in the transmission of power between Visigoths and Arabs after the fall of the kingdom of Toledo.